EVALUATION OF THE KIRK PATRICK MODEL FOR ENTREPRENEURSHIP COURSES IN THE MANAGEMENT AND ACCOUNTING STUDY PROGRAM AT THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITAS WIJAYA KUSUMA SURABAYA (UWKS) - Adrianto Trimarjono; Gimanto Gunawan; Djojo Dihardjo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This research provides a description of how the Kirkpatrick Evaluation Model is implemented in evaluating the Entrepreneurship Course for Management and Accounting students at the Faculty of Economics and Business, Universitas Wijaya Kusuma Surabaya. Evaluation tools varied across the model's four levels. The assessment of student outcomes, like business plan proposals, was conducted through performance evaluation. Adopting a mixed-methods descriptive design, the research applies qualitative and quantitative analysis, with an independent sample t-test used to examine differences. Participants included 60 students from the Management and Accounting Study Programs within the Faculty of Economics and Business at Universitas Wijaya Kusuma Surabaya. Data were gathered via closed questionnaires, and the reliability of these instruments was verified using Cronbach's Alpha. Student learning evaluation was obtained through performance assessment rubrics. The results indicate that the Kirkpatrick Evaluation Model in the Entrepreneurship Course Learning Program is highly effective, and there is no significant difference between students in the Management and Accounting study programs.